Environmental carrying capacity and economic feasibility of mangrove-based coastal ecotourism - Agus, Fadilatur Rahmi; Setyoadi, Rafi Fikri; Irnawan, Rahman Fajar; Viena, Winda Carla; Daza, Yaniza Dela (Institute of Advance Science, Social, and Sustainable Future, 2025)
Background: This study aims to analyze the economic feasibility and environmental impact of coastal tourism development using an Environmental Economy approach. The research is grounded in the urgency of promoting sustainable local economic development, particularly in coastal areas that hold high tourism potential but are vulnerable to environmental degradation. Methods: The methods employed include primary and secondary data analysis, in-depth interviews, direct observation, and Environmental Cost and Benefit Analysis. Findings: The findings indicate that the development of the Cemara Sewu Beach tourism area is economically feasible, with a benefit-cost ratio of 1.77 and a net present value (NPV) of IDR 129,611,000. Environmentally, the area demonstrates sufficient carrying capacity, with community-based management identified as a key factor in ensuring sustainability. Conclusion: In conclusion, the project is viable and should be pursued using an environmental economic approach that balances economic gains with ecological conservation. Novelty/Originality of this article: The novelty of this research lies in the integrated application of economic feasibility analysis and environmental carrying capacity assessment as a unified framework for sustainable tourism planning.